Faith in the Great Physician Suffering and Divine Healing in American Culture, 1860-1900 - Curtis, Heather D. (Johns Hopkins University Press, 2007)
Recipient of the Frank S. and Elizabeth D. Brewer Prize of the American Society of Church History for 2007Faith in the Great Physician tells the story of how participants in the evangelical divine healing movement of the late nineteenth century transformed the ways Americans coped with physical affliction and pursued bodily health. Examining the politics of sickness, health, and healing during this period, Heather D. Curtis encourages critical reflection on the theological, cultural, and social forces that come into play when one questions the purpose of suffering and the possibility of healing.Curtis finds that advocates of divine healing worked to revise a deep-seated Christian ethic that linked physical suffering with spiritual holiness. By engaging in devotional disciplines and participating in social reform efforts, proponents of faith cure embraced a model of spiritual experience that endorsed active service, rather than passive endurance, as the proper Christian response to illness and pain. Emphasizing the centrality of religious practices to the enterprise of divine healing, Curtis sheds light on the relationship among Christian faith, medical science, and the changing meanings of suffering and healing in American culture.